Strengthening Cryptographic Systems with AI-Enhanced Analytical Techniques - Chaganti, Krishna; Paidy, Pavan (International Journal of Applied Mathematical Research, 2025)
This study paper uses advanced Artificial Intelligence (AI) analytical tools to enhance cryptographic systems and counter evolving security threats. The proposed approach integrates traditional cryptographic techniques with Machine Learning (ML) to improve key management, encryption algorithms, and overall system security. This methodology is further strengthened by integrating the Cyber-Kill Chain (CKC) and the National Institute of Standards and Technology (NIST ) Cybersecurity Framework. In CKC’s stage model, Reconnaissance, Weaponization, and Exploitation are related to the NIST phases of Identifying, Protecting, Detecting, Responding, and Recovering as a comprehensive cybersecurity plan. Bayesian networks, Markov Decision Processes, and Partial Differential Equations (PDE) are referenced for threat detection, temporal modeling of vulnerabilities, and mathematical correctness, respectively. Introducing such optimizations promoted by AI into the CKC and NIST frameworks helps the proposed system achieve better flexibility, robustness, and extensibility. Additionally, reinforcement learning is explored to dynamically adjust security measures based on real-time threats. Experimental validation supports the efficiency of integrating AI-driven analytics into cryptographic frameworks. In this context, the work suggests a forward-looking plan for cybersecurity in contemporary society, mapping between theory development and applications that produce sound and secure cryptographic systems that neutralize cutting-edge security risks.